Droog design : 1991-1996 - Van Zijl, ida; Boyer, Maurice; Studio Gonnissen en Widdershoven (Utrecht : Centraal museum, 1997)
Droog Design ; Annink, Ed ; Bakker, Gijs ; Brekveld, Arian ; Buschmann, Roland ; Draisme, Eibert ; Franssen, Martijn ; Graumans, Rody ; Hessels, Paul ; van Hoff, Dick ; Hoogendijk, Martijn ; Hopman, Peter ; Hutten, Richard ; van der Jagt, Peter ; de Jong, Djoke ; Jongerius, Hella ; Konings, Jan ; Bey, Jürgen ; Möller, Andreas ; Oval ; Ramakers, Renny ; Remy, Tejo ; Visser, Arnout ; Wanders, Marcel ; Gonnissen, Nikki ; Widdershoven, Thomas
Nederlandse en Engelse tekst
boek
Keywords: Droog Design